PARIWISATA ISLAMI DI DANAU LAUT TAWAR KECAMATAN BINTANG KABUPATEN ACEH TENGAH - Ayu Kinnara (Departemen Sosiologi Universitas Sumatera Utara, 2013)
The Laut Tawar Lake is one of lake in Takengon, regency of central Aceh. The potency of the natural panorama of the lake is same as other tourism object in Nanggroe Aceh Darussalam (NAD). The beautiful panorama and the fresh air in addition to the history of the lake and any new finding as the tourism object that satisfy its visitors. As well as the enforcement of Isamic Shari’a, this tourism object to be Islamic based tourism object. The problem in this research is what a respond of the local people to the development of tourism object of Laut TAwar Lake by the implementation of Islamic Shari’a. Based on the result of research it concluded that since the enforcement of Islamic Shari’a, it also applied the Islamic based tourism, while it has not yet implemented actually because there is not socialization either by the officers of Islamic Shari’a Office oicer Tourism Office . Therefore, the local people did not know this Islamic tourism. Keywords : Tourism, Tourism Development, Islamic Shari’a, Tour.